ANALYSIS OF STRATEGIC PLANNING TOOLS FOR AGRICULTURE DEVELOPMENT - STEPANETS, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article considers SWOT and PEST analyzes as methods and tools of strategic planning of agriculture. The process of applying marketing research in the market of agricultural enterprises was studied. The strengths and weaknesses, opportunities and threats of agriculture were analyzed, the most important ones were outlined, namely, the great potential of the chernozems of Ukraine; significant volumes of agricultural products are exported as raw materials (wood, rapeseed, sunflower seeds, soybeans, oil, wheat, corn); shortcomings of legislation; obtaining and transferring the experience of European countries in the field of agriculture. The impact of macro-environmental factors on the results of the current and future activities of the industry was also considered and evaluated. The key trends in the development of agriculture in the world and in Ukraine were identified, which made it possible to form clear criteria for strategic planning methods. Key advantages for foreign investments in agriculture are identified.Strengths, Weaknesses, Opportunities and Threats (SWOT), as well as Politic, Economic, Social and Technological (PEST) segments are popular among agribusinesses. The study showed that many agricultural companies perform SWOT and PEST analyzes during strategic planning, quality control of the formation of state policy and legislation. SWOT activity requires a lot of attention, in particular, during the development and promotion of new strategies of many branches in agriculture. Mostly, many agricultural enterprises conduct a SWOT analysis at the stage of strategic planning, trying to apply and study the existing resources, both internal and external, examining their trends and patterns that can have either a positive or negative impact on the agricultural business. In the digital era, there are many changes in business strategies, including organizational policies. A limitation may be complex issues related to foreign organizations or commercial structures where SWOT analysis may fail. It cannot identify priority problems and not provide alternative solutions, time can use managers a large amount of information and data obtained through SWOT analysis and PEST analysis, the quality of data and information, including types and sizes of data, can have a significant impact on the construction of strategic decisions and implementation.
Keywords: strategic analyses; strategic planning; marketing research; methods; SWOT analysis; PEST analysis; marketing; strategy; agriculture